Maksimalisasi detoks media digital di era 4.0 - Mardatillah, Mardatillah (Maliki Interdisciplinary Journal, 2023)
Maximizing digital media detox. Currently we are in the 4.0 era, which is commonly known as cyber physical system, namely the collaboration between cyber technology and automation technology. So humans are used to living side by side with technology. In a day, the average person uses digital media without knowing the boundaries of space and time, this causes physical and psychological problems. To reduce addiction, users need a digital media detox.